Diplomasi Maritim Indonesia Dalam Indian Ocean Rim Association (IORA): Indonesian Maritime Diplomacy within the Indian Ocean Rim Association (IORA) - Aprilia Chairun Nisa (JOURNAL OF GOVERNMENT SCIENCE, 2020)
By 2014, as a follow up the 1982 Djuanda Declaration, Indonesian President Joko Widodo initiated and promoted the idea of making Indonesia a World Maritime Axis. Indonesian leadership in IORA from 2015 to 2017 was a stepping stone and media effort to realise such a national interest, and various form of diplomacy have been carried out within and through this organisation.  The connectivity between pillars of this World Martitime Axis and priorities of IORA strategic issues became an advantage in promoting such a concept. This article examines Indonesia’s national interests and maritime diplomacy practices carried out through this major initiative.  Keywords: national interests, maritime diplomacy, IORA, world maritime axis